New species of Pseudosinella Schäffer, 1897 (Collembola, Entomobryidae) from Hungary - Winkler, Daniel; Mateos, Eduardo (Zootaxa, 2018)
Two new species of the genus Pseudosinella Schäffer, 1897 from Hungary are described and illustrated. Characters shared by both species are the number of eyes (0+0), the labial chaetotaxy (M1M2rEL1L2) and the chaetotaxy of abdominal segment II (pABq1q2). P. csafordi sp. nov., characterized by dorsal macrochaetae formula R0R1R2R3TP/32/0201+2s, inhabits alluvial forests, while P. dungeri sp. nov., characterized by dorsal macrochaetae formula R0R1sR1R2TP/10/0201+2, was collected from a mid-montain steppic grassland.